Modelagem diferenciada para pessoas com desvios posturais: Técnicas particulares de modelagem que visam atender um nicho de mercado inexplorado (ModaPalavra e-periódico, 2012)
Nowadays, is observed a development in the fashion sector specialized in attending specific cases, but it is notable that it still needs more attention from the entrepreneurs of the area. The present article aims to adapt patternmaking of Haute Couture garments to women that possess postural deviations. The paper presents, through bibliographic search, the contribution of the authors that base subjects related to the theme, as well as results of the field research applied with the target. Furthermore, it is presented the carried out activities and the achieved results
Keywords: draping; Haute Couture; postural deviations